Public Duty versus Private Information: Jury Privacy in the Information Age - Natalia Antolak-Saper (Bond Law Review)
The lay-jury remains a central feature of justice systems in many common law countries. Underpinning the nature of jury trials are two fundamental principles: representativeness and impartiality. In order to satisfy these principles, jurors will typically be asked to provide personal information. This disclosure presents the possibility that a juror’s private information may be misused. While such concerns have existed for some time, the advent of Information Communication Technologies has given them increased urgency. Surveys reveal that a significant number of jurors are concerned for their privacy and safety, presenting a conflict between the public duty of jury service and their personal right of privacy. This article considers the extent to which the state can and should protect the privacy of individuals called for jury service. Focusing on examples from Australia, Canada, the United Kingdom and the United States, it begins with a discussion of the extent to which jurors are required to disclose personal information. It then discusses various concerns that may arise as a result of that disclosure, particularly personal safety and public embarrassment. Finally, suggestions for reform are provided in an attempt to address these concerns.